El espectáculo en las sociedades modernas : a propósito de dos tesis de Debord. (2017)
In this article, I make a critical assessment of two theses by Guy Debord on the place of the spectacle in modern societies, according to the first chapter of La société du spectacle. The first poses that the spectacle pursues no end beyond itself. The second is that the prevalence of the spectacle in modern societies justifies the belief in a dichotomy between appearance and reality. From the analysis of scientific communication and propaganda, I raise some doubts about the first. From philosophical criticism to the dichotomy, I show the same for the second. My conclusion inquiries about the relevance of these two theses in analyzing the place of the spectacle in modern societies.